Economic Sector Potential Analysis of Kutai Kartanegara and Penajam Paser Utara Regencies in East Kalimantan as Indonesia's New Capital City - Miska Pudhenta Nuke Saputri; Didit Welly Udjianto; Diah Lufti Wijayanti (AIBPM Publisher, 2024)
Indonesia plans to relocate its capital from Jakarta to East Kalimantan (IKN) to promote balanced development. The 15 to 20 years IKN megaproject necessitates regional development planning and economic assessments for Kutai Kartanegara and Penajam Paser Utara Regencies. This study aims to identify and analyze the leading economic sectors in Kutai Kartanegara and Penajam Paser Utara. Leading sectors and the structure of regional economies can be identified through (1) Location Quotient (LQ) analysis to determine the base and non-base sectors and (2) Shift-Share analysis to determine changes and shifts in economic structure. The research utilized secondary data in the form of time series of Gross Regional Domestic Product (GRDP) for Kutai Kartanegara and Penajam Paser Utara Regencies from 2013 to 2022. The analysis of Kutai Kartanegara Regency revealed three basic sectors and fourteen non-basic sectors. North Penajam Paser Regency, on the other hand, has ten basic sectors and seven non-basic sectors. The shift-share analysis results indicated that the economic sectors in Kutai Kartanegara Regency are superior, prospective, and mainstay sectors. Meanwhile, in Penajam Paser Utara Regency, the leading, prospective, mainstay, and lagging sectors.